Phylogenomic study of spiral-horned antelope by cross-species chromosome painting - Rubes, Jiri; Kubickova, Svatava; Pagacova, Eva; Cernohorska, Halina; Di Berardino, Dino; Antoninova, Marketa; Vahala, Jiri; Robinson, Terence J (Chromosome research, 2008)
Chromosomal homologies have been established between cattle (Bos taurus, 2n = 60) and eight species of spiral-horned antelope, Tribe Tragelaphini: Nyala (Tragelaphus angasii, 2n = 55male/56female), Lesser kudu (T. imberbis, 2n = 38male,female), Bongo (T. eurycerus, 2n = 33male/34female), Bushbuck (T. scriptus, 2n = 33male/34female), Greater kudu (T. strepsiceros, 2n = 31male/32female), Sitatunga (T. spekei, 2n = 30male,female) Derby eland (Taurotragus derbianus 2n = 31male/32female) and Common eland (T. oryx 2n = 31male/32female). Chromosomes involved in centric fusions in these species were identified using a complete set of cattle painting probes generated by laser microdissection. Our data support the monophyly of Tragelaphini and a clade comprising T. scriptus, T. spekei, T. euryceros and the eland species T. oryx and T. derbianus, findings that are largely in agreement with sequence-based molecular phylogenies. In contrast, our study suggests that the arid adaptiveness of T. oryx and T. derbianus is recent. Finally, we have identified the presence of the rob(1;29) fusion as an evolutionary marker in most of the tragelaphid species investigated. This rearrangement is associated with reproductive impairment in cattle and raises questions whether subtle distinctions in breakpoint location or differential rescue during meiosis underpin the different outcomes detected among these lineages.
Keywords: karyotypizace; In Situ Hybridization, Fluorescence; Evolution, Molecular; Female; Chromosomes, Mammalian; přežvýkavci; Species Specificity; savčí chromozomy; genomika; fylogeneze; druhová specificita; hybridizace in situ fluorescenční; mužské pohlaví; Ruminants; zvířata; Chromosome Painting; ženské pohlaví; Animals; malování chromozomů; Male; Karyotyping; Phylogeny; molekulární evoluce; Genomics